A New Species of the Ant Genus Vombisidris Bolton, 1991 (Hymenoptera: Formicidae: Myrmicinae) from Thailand - Jeenthong, Tadsanai; Jaitrong, Weeyawat; Tasen, Wattanachai (Tropical Natural History, 2023)
A new species of the ant genus Vombisidris Bolton, 1991 is described from southern Thailand under the name Vombisidris satunensis sp. nov. based on the worker and queen castes. The new species can be distinguished from the other congeners in having a yellow head and mesosoma, a dark gaster, and a short and straight propodeal spine. The type series was collected from dead twigs hanging on a shrub at the forest edge. A key to the known species of the genus Vombisidris is provided.